2005
DOI: 10.1007/s00467-005-1896-7
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and epidemiology of end-stage renal disease in Dutch children 1987–2001

Abstract: In this retrospective study 351 children (<16.0 years) with end-stage renal disease (ESRD) accepted for renal replacement therapy (RRT) in the four Dutch pediatric centers were analyzed for the period 1987-2001. The data were compared with a previous study performed in 1979-1986. Eighty patients were of non-Dutch origin. An annual ESRD incidence of 5.8 patients per million of the child population (p.m.c.p.) was calculated, without significant changes with time. The final prevalence in Dutch children under 15 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 12 publications
6
26
1
Order By: Relevance
“…The distribution of diagnoses has also been affected over the years by the transplantation of infants, most of whom have structural abnormalities, whereas glomerulopathies and other diagnoses present later. The incidence of structural abnormalities of 44% in our study is similar to that reported for the Dutch cohort [24]. There has been a parallel increase in the proportion diagnosed antenatally which has now reached 50% [25].…”
Section: Discussionsupporting
confidence: 78%
“…The distribution of diagnoses has also been affected over the years by the transplantation of infants, most of whom have structural abnormalities, whereas glomerulopathies and other diagnoses present later. The incidence of structural abnormalities of 44% in our study is similar to that reported for the Dutch cohort [24]. There has been a parallel increase in the proportion diagnosed antenatally which has now reached 50% [25].…”
Section: Discussionsupporting
confidence: 78%
“…In the same period, 36/143 (25%) patients were transplanted, among whom 8/36 (22%) had a preemptive transplantation (one with a living related donor allograft). The median age at first transplantation was 5 years (interquartile range [3][4][5][6][7][8][9][10][11]. Among all transplanted children, 31/36 (86%) received a graft from cadaveric origin and 5/36 (14%) received a graft from a living-related donor.…”
Section: Renal Replacement Therapymentioning
confidence: 99%
“…Data from early human and animal studies suggested that UTI in the presence of VUR may cause renal scarring [3]. Various studies subsequently reported that 7-17 % of end-stage renal disease (ESRD) is associated with VUR [4][5][6], attributable chiefly to renal dysplasia rather than postnatal scarring. Based on the assumption that long-term antibiotic prophylaxis or surgical reimplantation would prevent UTI and subsequent renal scarring, these interventions became the standard clinical practice for the treatment of VUR.…”
Section: Introductionmentioning
confidence: 99%